حمزة بكوشه نشاطه التربوي والاصلاحي (1907-1994) - رزوق, محمد الطيب (University of Eloued جامعة الوادي, 2022)
تتمحور هذه المداخلة عل إبراز شخصية تربوية إصلاحية من منطقة وادي سوف ممثلة في شخص حمزه بكوشه (شنوف) ونشاطه التربوي والإصلاحي بداية بالمولد والنشأة، دراسته الأولى، نشاطه بالجزائر، أدواره المتنوعة سواء كانت صحفية أو أدبية أو نضالية، في الأخير تعرضت لبعض من مؤلفاته. لأتوصل في ختام هذا البحث إلى استنتاج مفاده أن حمزة بوكوشه يعد علم من أعلام وادي سوف خاصة والجزائر عامة، تمكن من أن يرتمي في أحضان جمعية العلماء المسلمين الجزائريين منذ نشأتها ويكون من الفاعلين فيها. Abstract : This intervention focuses on highlighting a reformist educational figure from the Oued Souf region represented in the person of Hamza Bakoucha (Chenouf) and his educational and reform activities beginning with birth and upbringing, his first study, his activity in Algeria, his various roles, whether journalistic, literary or militant, in the last I was exposed to some of his writings. At the end of this research, I came to the conclusion that Hamza Boukosha is one of the flags of Wadi Souf in particular and Algeria in general, who was able to fall into the arms of the Association of Algerian Muslim Scholars since its inception and be one of the actors in it.
Hamaza Bakoucha, hiseducational and reformactivities (1907-1994)
مداخلة
Keywords: حمزة بكوشة؛ النشاط الاصلاحي؛ النشاط التربوي؛ النشاط الأدبي؛ نضاله; Hamza Bakoucha; reform activity; educational activity; literary activity; his struggle